Pembatalan Ratusan Sertifikat Hak Atas Tanah Oleh Kantor Wilayah Badan Pertanahan Nasional Jawa Barat - Beny Hadinata Wangean (Fakultas Hukum Universitas Pancasila, 2018)
The increasing of the use of land could potentially cause legal problem to several parties. Even some of them have certificate proving the ownership of land, but such of certificate still able to become an object of annulment. There was a case of such annulment in Pengasinan Village, Depok City, through Administrative Court. That annulment then reflected the weakness of law in protecting certain person’s land, although he or she holds freehold title certificate. This study uses doctrinal research method. In this case study, there were hundreds of annulments of freehold certificates in Pengasinan Village, Depok City, through Administrative High Court of Jakarta’s Decision Number 296/B/2013/PT.TUN.JKT jo. Administrative Court of Bandung’s Decision Number 11/G/2013/PTUN-BDG as the result of the issuance of the Decree of Head of Agrarian Inspection Number 205.D/VIII/1964. The decree was issued to implement land reform program in Indonesia. Several factors could become the cause of such kind of legal problem in the land tenure context, among others, the inaccuracy from National Land Agency officer in issuance of certificates, the low-qualified judge’s decision in land dispute settlement, and also the characteristic of land dispute which is not only public, but also private.